Early age infection of Foot and Mouth Disease affects the reproductive performance in Frieswal males - MATHUR, A K; TYAGI, S; MANDAL, D K (The Indian Journal of Animal Reproduction, 2023)
Semen production performance of adult Frieswal bulls suffered from Foot and Mouth disease infection (FMD) at an early_ age (upto I yr) were compared with bulls of similar age group unaffected by FMD. A significant reduction in the semen donation wasevident in bulls suffered with FMD at early age as compared to unaffected bulls of similar age. The mean values of semen quality interms of volume (3.27±0.19 vs 4.0±0.19 ml) and mass motility (1.6±0.16 vs 2.5±0.10) were significantly lowered in males sufferedwith Rv!D. Study further revealed that freezable quality semen could only be obtained from only 20% of bulls suffered from FMD ascompared to 73% in non affected group. These findings indicate that FMD infection at early age (upto I yr) affects the future semenproduction performance in Frieswal bulls.
Keywords: FMD; crossbred bulls; semen quality